2019
DOI: 10.2991/ijndc.k.191118.001
|View full text |Cite
|
Sign up to set email alerts
|

Toward Affordable and Practical Home Context Recognition: –Framework and Implementation with Image-based Cognitive API–

Abstract: To provide affordable context recognition for general households, this paper presents a novel technique that integrate imagebased cognitive Application Program Interface (API) and lightweight machine learning. Our key idea is to regard every image as a document by exploiting "tags" derived by the API. We first present a framework that specifies a common workflow of the machine-learning-based home context recognition. We then propose a pragmatic method that implements the framework using the "image-as-a-documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…As follow-up studies [17,18] continue, our work is not limited to simply evaluating the capability of cognitive APIs, but more focus on the implementation of a flexible and efficient process for home context sensing. As we mentioned in Section 1, we are struggling to understand the coverage and limitation of different APIs towards specific home contexts, and reduce unnecessary data manual labeling and calling cognitive APIs process.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As follow-up studies [17,18] continue, our work is not limited to simply evaluating the capability of cognitive APIs, but more focus on the implementation of a flexible and efficient process for home context sensing. As we mentioned in Section 1, we are struggling to understand the coverage and limitation of different APIs towards specific home contexts, and reduce unnecessary data manual labeling and calling cognitive APIs process.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…We generally divide the t (the total number of labeled data) into three levels: (1) large scale (t > 10,000), (2) moderate scale (10,000 ≥ t ≥ 1000), (3) small scale (t ≤ 100). In the existing home context sensing approach with machine learning [17,18], with the complexity of recognition object and the number of the defined contexts increase by users, it still requires directly manually labeling a moderate scale of data for training and continually try to calling multiple cognitive APIs for feature extraction. However, for each defined home context, according to different capabilities by cognitive APIs, there will be a difference among difficult-to-train data.…”
Section: Introductionmentioning
confidence: 99%
“…Constructing a single classifier model is a basic and essential part of realizing fine-grained home context recognition. Unlike naive deep learning, we previously dedicated the features of images extracted from a single cognitive API, to apply to light-weight supervised machine learning [29].…”
Section: Preliminary Studymentioning
confidence: 99%
“…For this purpose, we are currently investigating techniques that integrate inexpensive camera devices, multiple image-based cognitive APIs, and light-weight machine learning. We previously encoded the tags of a single API to document vectors, then applied them into machine learning for the model construction [29]. However, we found that the accuracy significantly decreased for contexts with multiple people (e.g., "General meeting", "Dining together", "Play games").…”
mentioning
confidence: 99%
“…(2) Real-time analysis using a large number of computing resources required is unrealistic. (3) The possibility of leakage of information cannot be ignored when uploading data through the network as demonstrated in [ 34 , 35 , 36 ]. In this section, we introduce some related works from recent years.…”
Section: Related Workmentioning
confidence: 99%